(untitled) - Stewart, John Robert (Boston Burr Ridge, 2002)
This book and you will learn more about yourself, family, friends, coworkers, and strangers we meet in our daily lives and the meaning behind our communication. Communication = Relationship
Keywords: Interpersonal communication